Analisis Perbandingan Metode AHP dan MOORA Dalam Pengambilan Keputusan Pemilihan Sertifikasi Kompetensi - Sutinah, Entin; Agustina, Nani; Martini, Martini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Bina Sarana Informatika University (UBSI) is a private university in Indonesia with a large number of students across various study programs. This study focuses on the Information Systems program. A challenge was identified in determining the type of competency certification that aligns with students' interests and talents. The objective of this study is to compare two methods, namely AHP and MOORA, to assist students in selecting the appropriate certification. The criteria considered in this research include Student Interest, Market Demand, Certification Cost, Certification Duration, and Career Prospects. The three alternatives evaluated are the Database Proficiency Test, Program Analysis Competency Certification, and Programmer Certification. Data analysis using the AHP method showed that the Database Proficiency Test achieved the highest score of 0.41, followed by the Program Analysis Competency Certification with a score of 0.33, and the Programmer Certification with a score of 0.26. Similarly, data analysis using the MOORA method yielded comparable rankings: the Database Proficiency Test scored 0.303, the Program Analysis Competency Certification 0.287, and the Programmer Certification 0.276. After comparing the two methods, both AHP and MOORA produced the same results, with the Database Proficiency Test ranking first, followed by the Program Analysis Competency Certification and the Programmer Certification. This finding indicates that the Database Proficiency Test is the most preferred certification among students in the Information Systems program.